2023
DOI: 10.3133/sir20235054
|View full text |Cite
|
Sign up to set email alerts
|

Flood-inundation maps for an 8-mile reach of Papillion Creek near Offutt Air Force Base, Nebraska, 2022

Abstract: Digital flood-inundation maps for an 8-mile reach of Papillion Creek near Offutt Air Force Base, Nebraska, were created by the U.S. Geological Survey (USGS) in cooperation with the U.S. Air Force, Offutt Air Force Base. The flood-inundation maps, which can be accessed through the USGS Flood Inundation Mapping Program website at h ttps://www .usgs.gov/ mission-areas/ water-resources/ science/ flood-inundation-mapping-fim-program, depict estimates of the areal extent and depth of flooding corresponding to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The streamflow resulting in a water-surface elevation of 951.60 ft above NAVD 88 at outfall 10 was determined using the U.S. Army Corps of Engineers Hydrologic Engineering Center-River Analysis System (HEC-RAS) hydraulic model described in Strauch and Hobza (2023). The HEC-RAS hydraulic model (Strauch and Hobza, 2023) was developed to create a series of flood inundation maps that cover about an 8-mi reach of Papillion Creek from its confluence with Big Papillion Creek downstream to its confluence with the Missouri River (fig. 1).…”
Section: Flow-duration Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The streamflow resulting in a water-surface elevation of 951.60 ft above NAVD 88 at outfall 10 was determined using the U.S. Army Corps of Engineers Hydrologic Engineering Center-River Analysis System (HEC-RAS) hydraulic model described in Strauch and Hobza (2023). The HEC-RAS hydraulic model (Strauch and Hobza, 2023) was developed to create a series of flood inundation maps that cover about an 8-mi reach of Papillion Creek from its confluence with Big Papillion Creek downstream to its confluence with the Missouri River (fig. 1).…”
Section: Flow-duration Analysismentioning
confidence: 99%
“…3). Analysis using a HEC-RAS model (Strauch and Hobza, 2023) indicated that the threshold streamflow associated with a water-surface elevation of 951.60 ft in Papillion Creek at outfall 10 is about 771 ft 3 /s. Flow-duration analysis examined streamflow records at the Papillion Creek at Fort Crook (USGS site 06610795) streamgage, which is about 2.1 mi upstream from outfall 10, from October 1, 2012 to September 30, 2021, and determined that 120 streamflow events exceeded the 771-ft 3 /s streamflow threshold.…”
Section: Surface-water Drainage and Flow-duration Analysesmentioning
confidence: 99%